Policies for Territorial Development and Intermunicipality in Brazil:: Complementarities and Tensions (Sustainability in Debate, 2013)
In Brazil, the development inter-municipal consortia were created to finance social infrastructuresector (health, sanitation, education) before being recognized through a constitutionalamendment in 1998 and regulated by specific laws in 2005 and 2007. The territorial developmentpolicies are more recent; they began to be discussed in the late 1990s and implemented in the2000s. This paper is structured based on two case studies and examines the origin of these policytools, their complementarities and tensions, as well as the practices and strategies of the actorsin the process implementation combined or parallel these two policies that mobilize similarreferences, but in different times.